Implications of Hofstede’s Cultrual values in the Applications of accouting dimensions of Carporate Governance: A Field studay of the Reality of Joint Stock Companies in the Environment of the Kurdistan Region OF Iraq - Shahjwan Majid Mohammed; Waria Burhan Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This research intention is to analyze the relationship and the effects of Hofstede's six dimensions of cultural differences in applications of accounting dimensions of Corporate Governance. The study is based on certain crucial questions about the nature of the relationship and effects between independent variable (Hofstede's cultural value) and dependent variable (Applications of accounting dimensions of Corporate Governance), for this reason the hypotheses plan was designed through a group of major and minor hypotheses. In order to verify the validity of the hypotheses, the study/plan was tested more than once, and a questionnaire was used for the data collection. This study has followed a descriptive analysis method in describing the major and minor variables as well as analyzing relations and the effects between variables. Furthermore, the study has represented group of private corporates which are managed by public labor in which the number reaches 13, however, the number for this study's samples covered 10 companies only. Later, the hypotheses were tested through a number of statistical analysis and examinations via SPSS V.22 program. In this perspective, the research has a multiple conclusions and the most prominent one was the existing of positive morale relationship between cultural values of Hofstede's and applications of accounting dimensions of Corporate Governance, also, the existence of effects of cultural values of Hofstede in applications of accounting dimensions of Corporate Governance. After a thorough analysis The research has revealed , the key role impact in which the cultural values of Hofstede in accounting and auditing exercises in the working settings of companies in Kurdistan region in Iraq that goes toward lower Power Distance Index , and Collectivism, additionally, lower Uncertainty Avoidance Index and Femininity, Long Term Orientation, future planning and perseverance, and finally, Indulgence. Also, the study suggests some advices and recommendations such as the need considering the cultural element in composing accounting systems for countries and developing them as independent variable from other environmental variables. Besides, the necessity to support and improve awareness and understanding of dimensions of cultural variables of Hofstede and the importance of its role in establishing accounting and audit values as a component to the accounting perspective in corporate governance. Besides, the importance of doing more researches to find out the logical liaison between culture and managers' direction in the environment of companies in Kurdistan region as the manager's values tend to a great extent is the product to cultural work, that itself, has a direct affect on accountants, auditors and their exercises.